Extra-tropical atmospheric response to ENSO in the CMIP5 models - Margaret M. Hurwitz; Natalia Calvo; Chaim I. Garfinkel; Amy H. Butler; Sarah Ineson; Chiara Cagnazzo; Elisa Manzini; Cristina Peña-Ortiz (Climate Dynamics, 2014)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

Recommendation of short tandem repeat profiling for authenticating human cell lines, stem cells, and tissues - Rita Barallon; Steven R. Bauer; John Butler; Amanda Capes-Davis; Wilhelm G. Dirks; Eugene Elmore; Manohar Furtado; Margaret C. Kline; Arihiro Kohara; Georgyi V. Los; Roderick A. F. MacLeod; John R. W. Masters; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Viable Transgenic Goats Derived from Skin Cells - Esmail Behboodi; Erdogan Memili; David T. Melican; Margaret M. Destrempes; Susan A. Overton; Jennifer L. Williams; Peter A. Flanagan; Robin E. Butler; Hetty Liem; Li How Chen; Harry M. Meade; William G. Gavin; et al. (Transgenic Research, 2004)

Cell compartmentalisation in planctomycetes: novel types of structural organisation for the bacterial cell - Margaret Lindsay; Richard Webb; Marc Strous; Mike Jetten; Margaret Butler; Rebecca Forde; John Fuerst (Archives of Microbiology, 2001)

Conservation Genetics of North American Freshwater Mussels Amblema and Megalonaias - Margaret Mulvey; Charles Lydeard; Debra L. Pyer; Kimberly M. Hicks; Jayne Brim‐Box; James D. Williams; Robert S. Butler (Conservation Biology, 1997)
Freshwater bivalves are among the most endangered groups of organisms in North America. Efforts to protect the declining mussel fauna are confounded by ambiguities associated with recognition of distinct evolutionary entities or species. This, in part, is due to the paucity of reliable morphological characters for differentiating taxa. We have employed allozymes and DNA sequence data to search for diagnosably distinct evolutionary entities within two problematic genera of unionid mussels, Amblema and Megalonaias. Within the genus Amblema three species are recognized based on our DNA sequence data for the mitochondrial 16S rRNA and allozyme data (Amblema neislerii, A. plicata, and A. elliotti). Only one taxonomically distinct entity is recognized within the genus Megalonaias—M. nervosa. Megalonaias boykiniana of the Apalachicolan Region is not diagnosable and does not warrant specific taxonomic status. Interestingly, Megalonaias from west of the Mississippi River, including the Mississippi, exhibited an allozyme and mtDNA haplotype frequency shift suggestive of an east‐west dichotomy. The results of this study eliminate one subspecies of Amblema and increase the range of A. plicata. This should not affect the conservation status of “currently stable” assigned to A. plicata by Williams et al. (1993). The conservation status of A. elliotti needs to be reexamined because its distribution appears to be limited to the Coosa River System in Alabama and Georgia.